2019
DOI: 10.3390/ijms20071743
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Molecular Weight on the Antibacterial Activity of N,N,N-Trimethyl Chitosan (TMC)

Abstract: N,N,N-trimethyl chitosan (TMC) with 93% degree of trimethylation was synthesized. TMC and the chitosan starting material were subjected to acidic hydrolysis to produce 49 different samples with a reduced average molecular weight (Mw) ranging from 2 to 144 kDa. This was done to allow the investigation of the relationship between antibacterial activity and Mw over a wide Mw range. NMR investigation showed that hydrolysis did not affect the degree of trimethylation (DSTRI) or the structure of the polymer backbone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…Among the 60 PCP used in this study, MW, Zagreb group indexes, Kier shape, logP, MR, and the number of bonds (aromatic, heavy) had the highest predicted impact on the antimicrobial activity and spectrum of activity of the SM, which is in accordance with previous studies [ 31 , 32 , 33 , 34 , 35 ]. Interestingly, the precision of the in silico model was greater (up to 100% prediction accuracy) with broad-spectrum hits (SM with antimicrobial activity against at least seven species).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Among the 60 PCP used in this study, MW, Zagreb group indexes, Kier shape, logP, MR, and the number of bonds (aromatic, heavy) had the highest predicted impact on the antimicrobial activity and spectrum of activity of the SM, which is in accordance with previous studies [ 31 , 32 , 33 , 34 , 35 ]. Interestingly, the precision of the in silico model was greater (up to 100% prediction accuracy) with broad-spectrum hits (SM with antimicrobial activity against at least seven species).…”
Section: Discussionsupporting
confidence: 91%
“…A total of the 34 PCP were correlated with the activity spectrum of the SM. Several of these parameters (e.g., MR [ 32 ], logP [ 30 , 36 ], HBD [ 37 ], hydroxyl groups [ 38 , 39 , 40 ], aromatic groups [ 41 ], MW [ 31 ], carbons atoms [ 42 ], pyrophosphate [ 43 ], double bonds [ 44 , 45 ], and boron [ 46 ]) are known to influence the antimicrobial activity of a molecule. It was also shown that, for clusters X and W, the number of carboxylic acid groups and HBD per SM were positively correlated with the spectrum of activity, while the number of acyl groups per SM were negatively correlated.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have investigated the effect of the addition of chitosan in solution or as part of a paste formulation, and found that, while chitosan enhances the effects of fluoride compounds, it often does not have an antimicrobial effect in these formulations [ 58 ], and one of the reasons for this could be linked to the high molecular weight employed in these studies. As the main aim of adding chitosan to fluoride salts containing formulas is that of increasing the overall viscosity, high molecular weight chitosan are favored; these, however, have a lower solubility, require an acidic solvent, and have a lower antimicrobial activity [ 58 , 59 ]. Based on these previous findings, we prepared low molecular weight chitosan derivatives and formed fluoride salts using the protonated chitosan as the counterion.…”
Section: Discussionmentioning
confidence: 99%
“…MW reduction is a common way to improve their solubility/viscosity and biological properties (Journot et al, 2020;Mohan et al, 2020). Insect chitin and chitosan with a low MW have higher antimicrobial, antioxidant, and wound healing activities (Sahariah et al, 2019) and exhibit excellent antiseptic and anticancer properties useful for drug development (Mohan et al, 2020). However, according to Davydova et al (2016), the main contribution to the antiinflammatory activity of chitosan was driven by structural elements that make up its molecule but not depending on MW.…”
Section: Chitin and Chitosanmentioning
confidence: 99%